KARAKTERISTIK FISIK, KIMIA, DAN SENSORIS FLAKES PISANG KEPOK SAMARINDA (Musa paradisiaca balbisiana) DENGAN SUBSTITUSI PATI GARUT - Mahmudah, Nur Aini; Amanto, Bambang Sigit; Widowati, Esti (Jurnal Teknologi Hasil Pertanian, 2017)
Banana-based flakes has a  foible properties of less crunchy texture. The level of crispness in the products is affected by the amylose content in its material. Substitution of arrowroot starch which has relative high amylose content is expected to improve the texture and product characteristics of banana flakes. The experimental design in this study used completely randomized design (CRD) by one factor, namely the variation of substitution of arrowroot starch with comparison banana’s flour: arrowroot starch are F1 (100%:0%), F2 (95%:5%), F3 (90%:10%), F4 (85%:15%). Sensory analysis was conducted using preference test (scoring) and also ranking. The data was analyzed by One-way ANOVA method and continued with Duncan Multiple Range Test Analysis if there is a significant difference (at significance level α = 0.05). Based on the results of sensory analysis, F4 formula is a formula of the most preferred by consumers from the aspect of color, flavor, texture (crispness), and overall. Physical analysis flakes shows that F4 has the lowest hardness value (27.07 N), a maximum resistance crunchy time in milk of 5.88 minutes and the greatest water absorption 133.05%. Chemical analysis F4 flakes with composition 85% of banana flour and 15% of arrowroot starch has moisture content (wb) 3.13%, ash content (wb) 2.25%, fat content (wb) 6.84%, protein content (wb) 0.57%, carbohydrate content (wb) 87.19%, starch content 72,46%, amylose and amylopectin content of 14.01% and 1.86%, crude fiber content 1.86%.